The Influence of Motivation and Tourist Visiting Interest on Joy of Missing out (JOMO) to the Bogor Botanical Gardens Tourist Destination - Rhomanhova, Zika Aqlia; Dewi, Liliana (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to analyze the effect of tourist motivation and interest in visiting on Joy of Missing Out (JOMO) at the Bogor Botanical Gardens tourist destination. JOMO describes the emotional satisfaction and self-awareness of tourists who enjoy tranquility and mindful experiences without digital social pressure, as opposed to the Fear of Missing Out (FOMO) phenomenon. This study employs a survey method in conjunction with an associative quantitative methodology. A questionnaire was used to gather data form 135 respondents who were chosen using purposive sampling. Because the data was not regularly distributed, Spearman’s correlation test was used for the study. The findings demonstrated a significant positive correlation between tourist motivation and JOMO (r=0.673; p<0.001), while tourist interest in visiting showed a very strong positive relationship with JOMO (r=0.760; p<0.001). Simultaneously, both variables significantly influenced the formation of JOMO behavior. These findings indicate that the higher the motivation and interest of tourists to seek calm and reflective experiences, the greater their tendency to enjoy tourism that focuses on inner balance and self-awareness. Thus, the Bogor Botanical Gardens has the potential to become a slow travel destination that supports a sustainable tourism lifestyle and the psychological well-being of tourists.